Monetary policy effects in times of negative interest rates: What do bank stock prices tell us? - Bats, Joost V.; Giuliodori, Massimo; Houben, Aerdt C.F.J. (Journal of Financial Intermediation, 2023)
This paper investigates bank stock performance following different monetary policy actions in times of positive and negative interest rates. Controlling for the broader stock market, monetary policy announcements that cause an unanticipated downward shift in the yield curve and a flattening of the shorter-end of the yield curve are found to persistently reduce bank stock prices once the interest rate environment is negative. Consistent with the deposits channel of monetary policy, the effects are larger and more persistent for banks that are relatively dependent on deposit funding. By contrast, a surprise movement in the slope of the longer-end of the yield curve does not impact bank stock prices in times of negative interest rates. Accounting data confirm that a parallel drop in the yield curve following a monetary policy decision in a negative interest rate environment hurts banks through shrinking deposit margins.